Mapping the scientific research on the ionizing radiation impacts on polymers (1975–2019) - Girard-Perier Nina (De Gruyter, 2021)
A bibliometric approach allowed us to study the global research trend on the impact of ionizing irradiations on polymers from 1975 to 2019. The investigation revealed 1,015 publications with growing interest since 1990. The research is split into three main categories: polymer science, nuclear science technology, and chemistry physical. The three main ionizing irradiations studied in this research are gamma, electron beam, and X-ray irradiations. The impact of ionizing irradiations on polymers under gamma irradiation is the most commonly studied field with 578 publications among the 1,015 publications. Electron beam irradiation is the second most studied field followed by X-ray irradiation. Whatever the irradiation modalities, publications focus on material degradation and material improvement studies.